Croissance et étude parasitaire du poisson Sarpa salpa peuplant le golfe d’Annaba. - GUENAOUI Maissa; YAHIA Marwa (My University, 2024)
The present study focuses on the growth and the parasitismof the specie Sarpa salpa which is a saltwater fish. A total of 51 specimens of S. salpa were collected from the Gulf of Annaba, during the summer period of 2018. The direct scalimetry method was used to study age. This method showed five age groups for the total population. Size frequency distributions and growth parameters were analyzed using STATISTICA 8 software. Von Bertalanffy parameters in the total Sarpa salpa population is found as follows: L∞=27.47, K=1.76, Ф=3.12. The weight growth of the total population is minor (b=2.9405). This study shows that parasitism has no influence on biological performance. ----------------------------------------------------------------------------------------------------------------------------- يرتكزهذاالعملعلىدراسةنمونوع من أسماكالمياهالمالحةSarpa salpa. جمعنا 51 عينةمنهذا السمك منخليجعنابةخلالصيف .2018 استخدامنا الطريقة المباشرة لدراسةالعمر،وهي طريقة الحراشف ،أظهرتهذهالطريقةخمسمجموعاتعمريةلإجماليالمجموعة. تمتحليلتوزيعاتتواترالحجموعواملالنموباستخدامبرنامج STATISTICA 8 . حسابمعاملاتفونبرتالانفيفيإجماليتعدادهذا السمك كان كالاتي: L∞=27.47, K=1.76, Ф=3.12. اظهرت النتائج ان نمو الوزن الاجمالي للافراد كان منخفضا(b=2.9405) . تبينهذهالدراسةأنالتطفلليسلهتأثيرعلىالأداءالبيولوجي. ------------------------------------------------------------------------------------------------------------------------------ La présente étude porte sur la croissanceet le parasitismed’une espècedu poisson marin Sarpa salpa. Un total de 51 spécimens de S. salpaa été collecté du golfe d’Annaba, durant la période estival de 2018. La méthode directe de la scalimétrie a été utilisé pour l’étude de l’âge. Cette méthode a montré 5 groupes d'âge pour la population totale. Les distributions de fréquence de taille et les paramètres de croissance ont été analysés selon l”utilisation de logiciel STATISTICA 8. Le calcul des paramètres de Von Bertalanffy chez la population totale de Sarpa salpa est trouvé comme suit : L∞=27.47, K=1.76, Ф=3.12.La croissance pondérale de la population totaleest minorante (b=2.9405). Nos résultats montrent que, le parasitismen’a aucune influence sur les performances biologiques.